La responsabilidad compartida de los hijos menores de edad en caso de divorcio controversial o de mutuo consentimiento; y la importancia de crear una norma legal que facilite su aplicación - Luna Aldaz, Martha Cecilia (2016)
Within the content of article 68 of the Constitution of the Republic, which says: To protect the rights of family members of persons: 1. Responsible parenthood be promoted; mother and father are obliged to care, upbringing, education, food, integral development and protection of the rights of their children, especially when they are separated from them for any reason. 2. Indefeasible family property in the amount and the conditions and limitations established by law is recognized. It guarantees the right to bequeath and inherit. 3. The State shall guarantee equal rights in decision making for the administration of the conjugal society and society of goods. 4. The State shall protect mothers, fathers and who are male and female heads of household in the exercise of their duties, and pay special attention to families dispersed for whatever reason. 5. The State shall promote maternal and paternal responsibility and monitor the implementation of the reciprocal rights and duties between mothers, fathers, daughters and sons. 6. Daughters and sons have equal rights regardless of filiation or adoption. 7 7. No declaration will be required on the quality of affiliation at the time. so that in this way the custody is necessary to create within the legal system the mechanism to ensure compliance with this constitutional principle as is the responsibility of parents in their obligations to their children if the marriage is dissolved, children after separation is in the same conditions as the state must protect minor children, to live in the best environment without problems from their parents, but consider who establishes custody is the judge in the judgment of dissolution of marriage. Do not confuse legal custody with parental authority. In case no joint custody, save in exceptional cases, parents still have the two parental rights over the children on time for child care are based on the idea that it suits the less frequent contact, significant and continuous with each parent. It is assumed that parents raise their children in important ways, which are aimed at the development and welfare of the child. They should also recognize that it is more difficult to program schedules parents when this involves separate households because it requires constant effort and communication between parents to promote what best suits the child involved. One child who is living apart their parents, have special needs regarding your relationship with them. The needs of a child and their ability to adapt to the situation of their parents change as the child matures. Parents need to be aware of these needs of the child at the time they are negotiating parenting time. They must be flexible and create a time led to the child's needs and circumstances. These standards are designed to help parents and the courts in the development of plans and represent the minimum time that parents should have with their children to maintain frequent and meaningful contact. And when it comes calls regular visits to emphasize the importance of time spent by parents with their son / daughter. The idea that the parent without custody "visit" the child does not indicate the reality of an ongoing relationship between the parent and the child. The minimum time that either parent without custody should spend with the child should not be interpreted as a time limitation imposed by the Court. It is not the purpose of these rules deprive parents of the right to agree or the Court to grant additional time or reduce as appropriate in each case. To cater to all situations related to parenting time, both parents must exercise sensitivity, flexibility and reasoning